Freedom as Non-Domination - Cueva Fernández, Ricardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
Neo-republicanism is a proposal mainly articulated by P. Pettit (1999 [1997]), although its grounds are previous historiographical works made by other authors. It aims to constitute a tertium genus in political philosophy that serves as a distinct option from both communitarianism and liberalism. However, Pettit’s intentions end up emptying the content of what would really be a republican position that, at the same time as integrating the old vision of classic authors and the findings of contemporary historiography, could link them to the democratic paradigm.